Controllable vapor phase growth of vertically aligned ZnO nanorods on TCO/Glass substrates. Issue 8 (3rd July 2014) - Dhanabalan, Sathish Chander; Garcia, John Paul; Calestani, Davide; Pattini, Francesco; Bissoli, F.; Villani, Marco; Rampino, Stefano; Zappettini, Andrea
<x xml:space="preserve">Abstract</x> Solution‐free and catalyst‐free vertically aligned ZnO nanorods have been synthesized by thermal CVD reactor at relatively low temperature (< 500 °C) to produce high‐surface 3D photoanode on glass substrate. The study revealed that size and orientation of ZnO nanorods are mainly related to TCO's grain morphology and crystallinity, while their length can be controlled by varying Zn evaporation parameters. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>